Emerging Safety Science: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
In recent years, the costs of new drug development have skyrocketed. The average cost of developing a new approved drug is now estimated to be $1.3 billion (DiMasi and Grabowski, 2007). At the same time, each year fewer new molecular entities (NMEs) are approved. DiMasi and Grabowski report that only 21.5 percent of the candidate drugs that enter phase I clinical testing actually make it to market. In 2007, just 17 novel drugs and 2 novel biologics were approved. In addition to the slowing rate of drug development and approval, recent years have seen a number of drugs withdrawn from the market for safety reasons. According to the Government Accountability Office (GAO), 10 drugs were withdrawn because of safety concerns between 2000 and March 2006 (GAO, 2006). Finding ways to select successful drug candidates earlier in development could save millions or even billions of dollars, reduce the costs of drugs on the market, and increase the number of new drugs with improved safety profiles that are available to patients. Emerging scientific knowledge and technologies hold the potential to enhance correct decision making for the advancement of candidate drugs. Identification of safety problems is a key reason that new drug development is stalled. Traditional methods for assessing a drug's safety prior to approval are limited in their ability to detect rare safety problems. Prior to receiving U.S. Food and Drug Administration (FDA) approval, a drug will have been tested in hundreds to thousands of patients. Generally, drugs cannot confidently be linked to safety problems until they have been tested in tens of thousands to hundreds of thousands of people. With current methods, it is unlikely that rare safety problems will be identified prior to approval. Emerging Safety Science: Workshop Summary summarizes the events and presentations of the workshop.
Keywords: Health and Medicine

Emerging Technologies and Innovation in Manufacturing Regenerative Medicine Therapies: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
As the number of regenerative medicines and therapies approved by the Food and Drug Administration (FDA) has grown to meet rising demand, the field of regenerative medicine has started to anticipate the potential of strategies such as artificial intelligence, decentralized manufacturing, and automation to accommodate this expansion. The National Academies Forum on Regenerative Medicine hosted a public workshop in October 2023 to explore emerging technologies, evolving manufacturing approaches, regulatory considerations, and diverse partnerships needed to increase regenerative medicine treatment capacity.
Keywords: Health and Medicine

Sex Differences in Brain Disorders: Emerging Transcriptomic Evidence: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Accumulating evidence gathered over the past three decades has demonstrated a biological basis for differences between men and women with respect to clinical features and treatment responses to several neuropsychiatric, neurodevelopmental, and neurodegenerative disorders. Dramatic sex differences have also been identified in the brain transcriptomes of individuals with multiple brain disorders, including depression, posttraumatic stress disorder, and autism. The brain transcriptome includes all of the messenger RNA as well as the non-protein-coding RNA molecules expressed in brain tissue and thus represents gene activity. To explore these sex-based transcriptomic differences further, the National Academies of Sciences, Engineering, and Medicine's Forum on Neuroscience and Nervous System Disorders hosted a workshop on September 23, 2020, titled Sex Differences in Brain Disorders: Emerging Transcriptomic Evidence and Implications for Therapeutic Development. The workshop brought together a broad spectrum of stakeholders to share cutting-edge emerging evidence, discuss challenges, and identify future opportunities and potential directions. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Improving the CDC Quarantine Station Network's Response to Emerging Threats - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Centers for Disease Control and Prevention (CDC) is responsible for preventing the introduction, transmission, and spread of communicable diseases into the United States. It does this primarily through the Division of Global Migration and Quarantine (DGMQ), which oversees the federal quarantine station network. Over the past two decades, the frequency and volume of microbial threats worldwide have continued to intensify. The COVID-19 pandemic, in particular, has prompted a reevaluation of many of our current disease control mechanisms, including the use and role of quarantine as a public health tool. The emergence of COVID-19 prompted CDC to request that the National Academies of Sciences, Engineering, and Medicine convene a committee to assess the role of DGMQ and the federal quarantine station network in mitigating the risk of onward communicable disease transmission in light of changes in the global environment, including large increases in international travel, threats posed by emerging infections, and the movement of animals and cargo. The committee was also tasked with identifying how lessons learned during COVID-19 and other public health emergencies can be leveraged to strengthen pandemic response. The report's findings and recommendations span five domains: organizational capacity, disease control and response efforts, new technologies and data systems, coordination and collaboration, and legal and regulatory authority.
Keywords: Health and Medicine

Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats: Annual Report 2021 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The wide-ranging portfolio of the standing committee’s work has illuminated many aspects of the COVID-19 pandemic and response efforts. This Annual Report summarizes the committee’s work in 2021 and highlights the short consensus study reports, rapid expert consultations, and meetings conducted during the year.

Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats: Annual Report 2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Since March 2020, the standing committee has consistently generated real-time policy recommendations and paved the way for the National Academies to produce an unprecedented amount of timely, evidence-based guidance in response to the COVID-19 pandemic. This Annual Report summarizes the committee’s work in 2020 and highlights the short consensus study reports, rapid expert consultations, meetings, and affiliated activities conducted during the year.

An Examination of Emerging Bioethical Issues in Biomedical Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On February 26, 2020, the Board on Health Sciences Policy of the National Academies of Sciences, Engineering, and Medicine hosted a 1-day public workshop in Washington, DC, to examine current and emerging bioethical issues that might arise in the context of biomedical research and to consider research topics in bioethics that could benefit from further attention. The scope of bioethical issues in research is broad, but this workshop focused on issues related to the development and use of digital technologies, artificial intelligence, and machine learning in research and clinical practice; issues emerging as nontraditional approaches to health research become more widespread; the role of bioethics in addressing racial and structural inequalities in health; and enhancing the capacity and diversity of the bioethics workforce. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Serious Illness Care Research: Exploring Current Knowledge, Emerging Evidence, and Future Directions: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To explore the current and future state of serious illness care research, the National Academies Roundtable on Quality Care for People with Serious Illness hosted a public workshop in November 2023. Speakers identified research gaps and challenges and explored strategies and opportunities to further develop the evidence base to improve care for all those living with serious illness, their families, and care partners.
Keywords: Health and Medicine

The Emerging Threat of Drug-Resistant Tuberculosis in Southern Africa: Global and Local Challenges and Solutions: Summary of a Joint Workshop by the Institute of Medicine and the Academy of Science of South Africa - Institute of Medicine (The National Academies Press, 2011)
Tuberculosis (TB) kills approximately 4,500 people worldwide every day. While most cases of TB can be treated with antibiotics, some strains have developed drug resistance that makes their treatment more expensive, more toxic and less effective for the patient. The IOM Forum on Drug Discovery, Development, and Translation and the Academy of Science of South Africa held a workshop to discuss ways to fight the growing threat of drug-resistant TB.
Keywords: Health and Medicine

A Study of Interactions: Emerging Issues in the Science of Adolescence: Workshop Summary - National Research Council; Institute of Medicine (The National Academies Press, 2006)
Scholars--and adults in general--have pondered for centuries the mysterious processes that influence the ways in which children gradually become adults. The development of professional organizations and journals devoted to adolescence, as well as increasing appreciation in academia and the world of policy for the importance of this phase of life, have helped this field catch up with the pace of research on other stages of human development particularly infancy and early childhood. The development of a comprehensive review of research on adolescence depends in large part on the perceived need for such a synthesis and the extent to which different research fields as well as policy and practice would benefit from such an effort. To address these issues, the National Research Council and the Institute of Medicine, through the Board on Children, Youth, and Families, held a two-day workshop in September 2005. The workshop was designed as an opportunity for an interdisciplinary group to explore the different strands of research that contribute to understanding adolescence. In the brief time available, the group was not asked to address the entire range of issues related to adolescent health and development, but rather to provide an initial explanation of issues that a longer term study might address. A Study of Interactions summarizes the major themes discussed at the workshop. It begins with an overview of what adolescence is and current views of the processes that shape development in the second decade of life. It explores the transdisciplinary research issues already presented in this field, as well as issues raised in discussions of goals for the field's future. A closing section describes the presenters' thoughts on the feasibility of launching an in depth contextual study that could more firmly establish connections among the many fields of study concerned with adolescence.
Keywords: Behavioral and Social Sciences; Health and Medicine

Health Systems Science Education: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Global Forum on Innovations in Health Professional Education held a public workshop in November 2023. Speakers explored how health professional educators and providers with health systems science (HSS) training can prepare learners to work together within health systems, resulting in better patient care, improved population health, and enhanced health professional well-being. Organizers hosted a public pre-workshop in October 2023 to create a foundational understanding of HSS prior to their workshop.
Keywords: Education; Health and Medicine

Nonhuman Primate Models in Biomedical Research: State of the Science and Future Needs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Nonhuman primates represent a small fraction of animals used in biomedical research, but they remain important research models due to their similarities to humans with respect to genetic makeup, anatomy, physiology, and behavior. Limitations in the availability of nonhuman primates have been exacerbated by the COVID-19 pandemic and recent restrictions on their exportation and transportation, impacting National Institutes of Health (NIH)-funded research necessary for both public health and national security. Additionally, there is continued interest in understanding whether and how nonanimal models can be used to answer scientific questions for which nonhuman primates are currently used. At the direction of the U.S. Congress, NIH asked the National Academies of Sciences, Engineering, and Medicine to convene an expert committee to conduct a landscape analysis of current and future use of nonhuman primates in NIH-supported biomedical research, as well as opportunities for new approach methodologies to complement or reduce reliance on nonhuman primate models. This report provides the committee findings and conclusions.
Keywords: Biology and Life Sciences; Health and Medicine

Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Recent events, including the COVID-19 pandemic and the collective awakening around issues related to racial justice, diversity, and inclusion, have underscored the challenges facing neuroscience and neuroscience training. To address these challenges, the Forum on Neuroscience and Nervous System Disorders of the National Academies of Sciences, Engineering, and Medicine convened a series of virtual workshops on neuroscience training with the goal of reconsidering how we think about neuroscience training in a rapidly changing world. On February 22, 2021, the fifth and final workshop in this series, titled Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World, brought together stakeholders from across the neuroscience ecosystem to discuss how the culture of science and scientific training can become more inclusive, balanced, and adaptive to changing times. This final workshop expanded on many issues raised in previous workshops, including the importance of mental health and well-being in academic research; how to resist the legacy of white supremacy and support diversity in academia; and how to redefine what success means for neuroscientists in both academic and non-academic settings. This publication summarizes the discussions that occurred at the workshop.
Keywords: Health and Medicine

Mitigating Health Disparities in Brain Disorders Starting with Basic Science: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Despite increased attention paid to health equity in recent years, disparities in health outcomes and access to care persist across disease areas, including in central nervous system disorders. The National Academies Forum on Neuroscience and Nervous System Disorders hosted a public workshop in November 2023 to reflect on strategies to advance equitable practices in neuroscience and improve data quality by engaging more diverse populations in the research process; acknowledging systematic, technological, and internal biases; and considering inclusive research models.
Keywords: Health and Medicine

Exploring the Use and Application of Implementation Science in Health Professions Education: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Implementation science bridges the gap between research and medical practice, investigating aspects of practice and pedagogy that make the strategies successful for future use. By introducing and training leaders, faculty, and health workforce researchers in implementation science, health professions education institutions can build capacity for evidence-based practices. The National Academies Global Forum on Innovation in Health Professional Education held a workshop series to introduce the concept of implementation science to health professional educators to consider its potential use in the classroom. Speakers provided a foundation for discussion of the role of implementation science in health professions education and provided methods for educators interested in applying these recommendations to scale. This Proceedings of a Workshop highlights the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

Exploring the State of the Science of Stem Cell Transplantation and Posttransplant Disability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Board on Health Care Services of the National Academies of Sciences, Engineering and Medicine hosted a virtual workshop, funded by the Social Security Association, to examine disability associated with hematopoietic stem cell transplantation. The workshop, held on November 15, 2021, included presentations on the functional outcomes for individuals who have received hematopoietic stem cell treatment, as well as medical advances, developments, and research in this area. This Proceedings of a Workshop highlights the presentations and discussions that occurred in the workshop.
Keywords: Health and Medicine

Exploring the State of the Science of Solid Organ Transplantation and Disability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Transplantation of a solid organ, such as a kidney, heart, or liver, is a lifesaving procedure and is sometimes the only viable treatment for patients experiencing end-stage organ failure as a result of illness or injury. A growing prevalence of solid organ diseases in the United States is contributing to more people needing a transplant and longer wait times on the national transplant waiting list. While transplantation can lengthen a person's life, the road to recovery is difficult and complex. Transplant recipients commonly experience considerable impairments related to health factors, medication side effects, organ rejection, or other setbacks that can cause functional limitations. A spectrum of services and supports can be beneficial to patient functioning and quality of life, but patient access is variable due to individual, system, and social factors. To gain an understanding of current scientific findings in the field of solid organ transplantation, the U.S. Social Security Administration asked the National Academies of Sciences, Engineering, and Medicine's Board on Health Care Services to organize a virtual public workshop to examine disability associated with organ transplantation. The workshop, held March 22-23, 2021, focused on kidney, heart, liver, and lung transplantation, and to a lesser extent intestine transplantation. Subject-matter experts presented on clinical aspects of post-transplantation recovery and described the implications for physical, cognitive, and psychosocial functioning in adults and children. This publication summarizes the presentations and panel discussions from the workshop.
Keywords: Health and Medicine

Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K–12, undergraduate, and graduate and professional levels.
Keywords: Education

Building Trust in Public Health Emergency Preparedness and Response (PHEPR) Science: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On March 29-30, 2022, the National Academies of Sciences, Engineering, and Medicine hosted a workshop aimed at examining the roles of trust and trustworthiness in the public health emergency and response (PHEPR) science enterprise - the institutions, the research process, and the researchers and practitioners - across the continuum of pre-event, event, response, and mitigation. The first day examined issues of trust in PHEPR science, where they originate, and what can be done to build and maintain trust in public health agencies. The second day shifted discussions to communication and strategies to address misinformation and ensure clear understanding of public health communications. The final session allowed workshop participants and public attendees - through an interactive Miro board session - to reflect on workshop discussions and share strategies to build public trust over the next 5 years. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

Population Health Science in the United States: Trends, Evidence, and Implications for Policy: Proceedings of a Joint Symposium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On October 3, 2018, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine and the Interdisciplinary Association for Population Health Science convened a joint symposium in Washington, DC to consider the current state of population health science in the United States. At the symposium, speakers and participants reviewed the status of population health in the United States, including current trends in health and mortality, and racial, ethnic, and socioeconomic disparities; explored the complexities of policy implementation with attention to evidence generation and to surfacing and mitigating negative unintended consequences of policies for population health; and shared perspectives on finding common ground to move population health forward. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine